2010
DOI: 10.1021/jp102655g
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Isoprene Hydroxyalkyl Peroxy Radical−Water Complexes (C5H8(OH)O2−H2O)

Abstract: Herein we report an extensive ab initio study on the existence of eight beta-hydroxy isoprene peroxy radical-water complexes. Binding energies calculated at the MP2(full)/6-311++G(2d,2p)//CCSD(T)/6-311++G(d,p) level of theory range between 3.85 and 5.66 kcal mol(-1). The results of natural bond orbital calculations are presented to help rationalize complex formation. Atmospheric lifetimes, equilibrium constants, heats of formation, and the relative abundance of complexed to uncomplexed peroxy radicals are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…The robust systematic searching method of Clark et al [11] was used to identify the lowest energy structure for the two hexanal radical isomers (2-hydroxy-3-peroxy hexanal and 2-peroxy-3-hydroxy hexanal radicals). The lowest energy structures of interest in this work were identified by rotating bonds C1AC2, C2AC3, C2AO2(OH), and C3AOH(O2) by 90…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The robust systematic searching method of Clark et al [11] was used to identify the lowest energy structure for the two hexanal radical isomers (2-hydroxy-3-peroxy hexanal and 2-peroxy-3-hydroxy hexanal radicals). The lowest energy structures of interest in this work were identified by rotating bonds C1AC2, C2AC3, C2AO2(OH), and C3AOH(O2) by 90…”
Section: Methodsmentioning
confidence: 99%
“…In recent work, Clark et al reported the binding energies and minimum energy structures for six different hydroxy isoprene peroxy (HIP) radicals that form complexes with water, with binding energies ranging from 3.9 to 5.7 kcal/mol [11]. Using a combination of the binding energies and natural bond orbital (NBO) analyses, they hypothesized that water complexation could potentially perturb the kinetics and product branching ratios of reactions involving these species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the HO 2 .H 2 O term has been included as an additional term for the calculation of the HO 2 þ HO 2 termination step (Sander et al, 2011), the water influence on the abundances of RO 2 throughout the troposphere has, up to now, been ignored in many atmospheric modelling studies. The energetics and potential impacts of hydroperoxyl radical-water complexes (HO 2 .H 2 O) and organic peroxy radical-water complexes (RO 2 .H 2 O) were presented in previous theoretical chemistry studies (Aloisio and Francisco, 1998;Clark et al, 2008Clark et al, , 2010Archibald et al, 2011) (Aloisio et al, 2000;Kanno et al, 2006). The estimation by Aloisio and Francisco (1998) showed that 29% of all HO 2 radicals present in the atmosphere could participate in water complexation under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium constant, K eq taken from the literature (Clark et al, 2008(Clark et al, , 2010 is used to calculate the RO 2 .H 2 O concentration. Aloisio and Francisco (1998) suggested that the RO 2 .H 2 O complexes could exist in significant abundance in the lower region of the atmosphere where conditions of high water density and low temperature could favour its formation.…”
Section: Introductionmentioning
confidence: 99%